The Role of E-Voting in Promoting Participation and Transparency in Elections: A Case Study of The Jembrana Village Head Election - Zahwa Nabila Putri Maharani; Labib Muttaqin (Proceeding International Conference Restructuring and Transforming Law, 2025)
This study explores the role of electronic voting (e-voting) in strengthening voter participation and ensuring transparency in elections, with a specific focus on its implementation in the Village Head Election (Pilkades) in Jembrana Regency, Bali. The research adopts a normative juridical method with a statute approach. It offers a novel perspective by providing an empirical evaluation of the effectiveness of e-voting at the village election level, highlighting its potential applicability to broader electoral contexts. The findings reveal that the implementation of e-voting in Jembrana has successfully increased voter turnout and ensured a more transparent and accountable election process. In conclusion, e-voting serves as an effective solution to address the challenges of traditional voting systems and can be replicated in other regions to strengthen local democracy, with potential for future integration into larger-scale elections.